2012
DOI: 10.1158/0008-5472.can-11-3472
|View full text |Cite
|
Sign up to set email alerts
|

Jab1/CSN5 Negatively Regulates p27 and Plays a Role in the Pathogenesis of Nasopharyngeal Carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is an Epstein-Barr virus-associated malignancy most common in East Asia and Africa. Aberrant expression of Jab1/CSN5, a negative regulator of the cell cycle inhibitor p27, is correlated with reduced p27 expression and associated with advanced tumor stage and poor prognosis in several human cancers. In this study, we examined the functional relationship between Jab1 and p27 protein expression in NPC. Immunohistochemical analysis showed an inverse association between Jab1 and p27 i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(112 citation statements)
references
References 28 publications
6
105
0
1
Order By: Relevance
“…Loss of Jab1/CSN5 expression sensitized both primary embryonic fibroblasts and osteosarcoma cells to γ-radiation-induced apoptosis. 5 It is interesting to note that our NPC studies showed that inhibition of Jab1/CSN5 expression with 5 nM of siRNA for 48 h was insufficient to induce apoptosis, 7 whereas higher doses of Jab1/CSN5 siRNA (10 or 20 nM) induced apoptosis (unpublished data), and knocking down Jab1/CSN5 expression in NPC cells increased UV radiation-, ionizing radiation-, and cisplatin-induced apoptosis. 4 In contrast, overexpression of Jab1/CSN5 in CNE1 NPC cells blocked UV radiation-and cisplatin-induced apoptosis.…”
Section: Jab1/csn5 Inhibition As a Novel Therapeutic Strategy Againstmentioning
confidence: 83%
See 3 more Smart Citations
“…Loss of Jab1/CSN5 expression sensitized both primary embryonic fibroblasts and osteosarcoma cells to γ-radiation-induced apoptosis. 5 It is interesting to note that our NPC studies showed that inhibition of Jab1/CSN5 expression with 5 nM of siRNA for 48 h was insufficient to induce apoptosis, 7 whereas higher doses of Jab1/CSN5 siRNA (10 or 20 nM) induced apoptosis (unpublished data), and knocking down Jab1/CSN5 expression in NPC cells increased UV radiation-, ionizing radiation-, and cisplatin-induced apoptosis. 4 In contrast, overexpression of Jab1/CSN5 in CNE1 NPC cells blocked UV radiation-and cisplatin-induced apoptosis.…”
Section: Jab1/csn5 Inhibition As a Novel Therapeutic Strategy Againstmentioning
confidence: 83%
“…For example, knockdown of Jab1/CSN5 inhibited proliferation and induced apoptosis in breast cancer cells 82 and, in our research, NPC cells. 7 Furthermore, Jab1/CSN5-deficient mice were found to have an embryonically lethal phenotype, suggesting that Jab1/CSN5 is critical for fetal development and survival. 5 Our previous studies showed that Jab1/CSN5-null embryos were smaller than wildtype embryos and displayed growth retardation.…”
Section: Jab1/csn5 Inhibition As a Novel Therapeutic Strategy Againstmentioning
confidence: 99%
See 2 more Smart Citations
“…The MTT assay was used to evaluate cell viability as previously described (17). Briefly, NPC cells were seeded in 96-well plates (2,000 cells/well) in RPMI-1640 medium with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%